NORMATIVE JURIDICAL ANALYSIS OF FORGERY OF AUTHENTIC DEEDS CARRIED OUT BY NOTARIES - Rizka Ayu Dwitami Hidayat; Siti Malikhatun Badriyah (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
The Notary Office Law does not explain the sanctions for Notaries clearly and in detail, only explaining on the Administrative and Civil Side, while Notaries cannot be said that Notaries are free from Criminal Sanctions, while the Notary's Office does not explain the Notary Criminal Sanctions section. Notaries can make mistakes such as committing intentional or unintentional forgery of deeds and these actions violate the Undang-undang Jabatan Notaris (UUJN) and the Notary Code of Ethics. From this case, administrative sanctions or code of professional ethics for the position of notary are imposed and civil sanctions can then become and be qualified as a criminal act committed by a Notary. The method is a descriptive analysis and use data analyzed qualitatively. This result is an explanation of how the application of criminal sanctions to Notaries who commit criminal acts of forgery of authentic deeds and the legal consequences of forgery of authentic deeds carried out by Notaries. As a result of the notary law, which is subject to criminal sanctions in the criminal act of forgery of authentic deeds along with deeds that are used as objects of the case in court for criminal cases, the notary defendant is sentenced to imprisonment and all deeds issued by the defendant's Notary are null and void.